Neoadjuvant prostate artery embolization prior to prostate radiation therapy: A single institution experience on the durability of clinical urinary improvement after radiation - Vaseem M. Khatri; G.Daniel Grass; Ram Thapa; Laura Maun-Garcia; Kujtim Latifi; Arash O. Naghavi; Aditya Garg; Daniel Fernandez; Javier Torres-Roca; Anupam Rishi; Omeed Jazayeri-Moghaddas; Julio Pow-Sang; et al. (Clinical and Translational Radiation Oncology)
Background: Radiation therapy (RT) for prostate cancer has gastrointestinal and genitourinary toxicities, greater with baseline lower urinary tract symptoms (LUTS) and larger prostate volume (PV). Prostate artery embolization (PAE) improves LUTS and PV before RT. This study evaluates the durability of LUTS improvement from neoadjuvant PAE before prostate RT and oncologic outcomes. Methods: We retrospectively identified patients receiving definitive prostate RT following PAE from a prospective database, including International Prostate Symptom Scores (IPSS), pre- and post-PAE MRI PV, and toxicity per CTCAEv5.0. Primary objective was LUTS by IPSS. Secondary objectives included biochemical recurrence-free survival (bRFS), local recurrence, and distant metastasis. Results: From 9/2017–5/2024, 82 patients underwent PAE before RT, with 30.5 % having unfavorable intermediate risk. RT consisted of conventional fractionation (n = 21), moderate hypofractionation (n = 42), SBRT (n = 11), and EBRT/brachytherapy boost (n = 8); a subset of patients received androgen deprivation therapy. Pelvic lymph nodes were treated in 28 (34 %) patients. Median pre-PAE IPSS was 18 (range 2–34), PV 90 cc (14.2–240), and PSA 8.4 ng/mL (0.02–125.5). Post-PAE, mean IPSS reduction was 10.7 points (−13–30). Mean PV reduction was 30.9 cc (−9–136) or 32 %. PAE converted 52 % of patients contraindicated by size/IPSS for brachytherapy/SBRT. Post-RT, mean IPSS changes at 3, 6, 12, 18 and 24 months were −8.7, −8.5, −9.5, −8.9, and −7.6, respectively (p < 0.001). At 24.2-month median follow-up, 1 local recurrence occurred. Two-year bRFS was 92 % for non-metastatic patients. Conclusion: Urinary improvement is durable after RT in men with large prostates and/or high LUTS burden with neoadjuvant PAE, and no increased risk of recurrence at intermediate-term follow-up. Further investigation is warranted.